Gênero, trabalho doméstico e de reprodução social : uma análise sobre a exploração e opressão de mulheres no capitalismo - Garcia, Rubya Souza (2022)
The present dissertation entitled GENDER, HOUSEHOLD WORK AND SOCIAL REPRODUCTION: an analysis of the exploitation and oppression of women in capitalism, aims to apprehend how capitalism benefits from the unpaid work of women, through the studies of Silvia Federici, with a view to contributing to the expansion of knowledge in the area of Social Work about domestic work and social reproduction. The investigative path was traced through three specific objectives, namely: 1) To apprehend the conceptions of the author Silvia Federici about domestic work and social reproduction; 2) Identify the contribution of domestic work and social reproduction in the dynamics of the reproduction of capitalism from the studies of Silvia Federici and. 3) Identify, based on the analysis of the works of Silvia Federici, which would be the possible contributions to the process of women's emancipation in the Brazilian reality with regard to domestic work and social reproduction. Considering these objectives, the research was built through the bibliographic, qualitative and exploratory matrix. In line with the qualitative perspective, the study aims to break with the apparent that is expressed in the immediacy of reality through the use of the critical dialectical method. As for the bibliographical productions, three works by the author Silvia Federici were selected to build the analysis, namely: The Calibã and the Witch: women's body and primitive accumulation (2017), The Zero Point of the revolution: domestic work, reproduction and feminist struggle (2019) and Women and Witch Hunt (2019) e o O Patriarcado do Salário (2021). The research revealed that unpaid domestic and social reproduction work performed by women encompasses a complex chain of care that goes beyond the limits of the private environment, constituting the most important product for the reproduction for the capitalist mode of production: the workforce. Capitalism, in turn, makes the work performed by women invisible under the cloak of affection as a characteristic that invalidates it as value-producing work so that they can continue to benefit from it. It was identified that, in addition to the categories of exploitation and oppression, in the reality of non-white Brazilian women, the category of expropriation is also expressed considering the country's colonial slavery heritage and the effects that reverberate from it.